FLOWERING SYNDROME – HYBRID PERFORMANCE RELATIONSHIP IN MAIZE 1- Field traits and growth rates - & et al., Al- Khazaali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
In order to identify the role of selection for early and late silking on the inbred lines from Maize (Zea Mays L.) regarding the grain yield of the consequent hybrids. Filed experiment for four seasons (spring and full 2014 and 2015) was conducted in the experimental field of Field Crop Dept., Coll. of Agric., Univ. of Baghdad. Four inbred lines (Zm19, Zm32, Zm51 and Zm61) and two testers (Zm21 late and Zm60 early silking) were used. In the first two seasons, the seeds of the four inbred lines were planted, first 10 plants that flowered early and 10 plants that flowered late were selected and the seeds of the selected plants were multiplied. The seeds of the early and late selected inbred lines were planted in the third season and crossed with testers. Crosses from the early and late flowering were produced and their seeds were cultivated in the last season. Comparison in some field and growth traits were conducted among the crosses. The experiments laid out in completely randomized block design (RCBD) at three replicates. Selection for early and late flowering parents has induced significant differences in days to flowering for all crosses and ranged between 62 days for early parents and 66 days for late parents. Also, significant differences were shown in several traits, the most prominent were crop’s and seed’s growth rate (CGR and SGR ), that correlated with seed filling duration (SFD), which contributed to increase the deposition of the dry matter into the grain for a longer period, which gave a high grain yield (GY). CGR of outstanding crosses ranged from 3.18 to 6.21 g.m-2.day, SGR ranged between 2.3 to 7.3 g. m-2.day, and the SFD between 35-38 days. In parallel, the testers (Zm21 late and Zm60 early silking) have significantly differed in their effect on the traits of some derived crosses, where the results showed significant superiority of the crosses Zm32Zm60 resulted from crossing the tester Zm60 with early silking parents selected from inbred line Zm32 on the crosses Zm32Zm21 resulted from crossing the tester Zm21 with the same parents of Zm32 in the traits of Total Dry Matter (TDM) (1.85 kg.m-2), CGR (18.28 g.m-2.day), Harvest Index (HI) (0.56), and SGR (3.3 g.m-2.day). It can be conclude  that selection for early and late silking inbred lines, as well as the effect of the early and late silking tester have a great importance in deriving hybrids of a high yield and distinct in several traits, which are all significantly contributing in increasing the GY.